KUASA POLITIK PEREMPUAN: STUDI TENTANG DINAMIKA KEPEMIMPINAN PEREMPUAN PADA PARTAI POLITIK ISLAM DI KABUPATEN GORONTALO - Kadji, Jurisman; Qohar, Abd; Wahyuni, Citra; Jurisman M. Kadji; Abd. Qohar; Citra Wahyuni (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study examines the dynamics of women's leadership in Islamic political parties. The National Awakening Party (PKB) and the National Mandate Party (PAN) in Gorontalo Regency are case studies. In this study, the author outlines several important findings related to the patterns and practices of power that occur. The purpose of this study is to explain the processes and obstacles that influence women's leadership in Islamic political parties in Gorontalo. The type of research used is qualitative research with a case study research method, namely an in-depth research approach to a particular case or phenomenon. The results of this study conclude that: there are different processes of women's political leadership demonstrated by each party leader. This is known from the patterns and interactions carried out to achieve the goals set with the power held as party leaders. In addition, several main factors were found that most dominant influence women's leadership in political parties, namely: 1) Culture and traditions that influence public perception, 2) Women's resource capacity in building political networks, 3) Political Party Support. All of these are the main factors that determine the success of women in exercising their power as leaders.